SENAM KAKI DIABETIK TERHADAP PENURUNAN GULA DARAH - Erwansyah, Luqi; Budianto, Apri; Tiara (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Diabetic foot exercise is a form of exercise for people with diabetes mellitus at all ages that can avoid, texiadizxa, open, sebiuzza, circulation. datab, in the foot section, is launched, during diabetic foot exercise blood flow increases sebinzza, more receptors, insulin is available, and the tenentat becomes more active, so that there is an increase in glucose use by the body which will ultimately result in, in the announcement, blood sugar. Objective: The purpose of this study was to determine the effect of diabetic foot exercise on the general, datab sugar, in people with diabetes mellitus in the Puskesmas Ambatava area in 2024. Methods: The research method used a quasi-experimental design with Tragedgan nonequivalent control group with a sample size of 22 people. The sampling technique used purposive sampling. Data analysis using the dependent sample t-test. Results: This study specifically recommends that individuals with diabetes mellitus perform diabetic foot exercises, as these exercises can help reduce blood glucose levels.